Financial Concerns and the Marginal Propensity to Consume in COVID Times : Evidence from UK Survey Data - Albuquerque, Bruno (IMF Working Papers; Working Paper ;, 2022)
We study how household concerns about their future financial situation may affect the marginal propensity to consume (MPC) during the COVID-19 pandemic. We use a representative survey of UK households to compute the MPC from a hypothetical transfer of pound 500. We find that household expectations play a key role in determining differences in MPCs across households: households concerned about not being able to make ends meet have a 20% higher MPC than other households. Our findings suggest that policies targeted to vulnerable and financially distressed households may prove more effective in stimulating demand than providing stimulus payments to all households.